Comparative Analysis of Preoperative Sedation Modalities: Oral Midazolam and Ketamine Versus Chloral Hydrate and Meperidine in Pediatric Tonsillectomy - A Randomized Clinical Trial - Nima Naderi; Soodabeh Emami; Mahsa Banifatemi; Maryam Ghadimi; Ensieh Shahriari; Mohammad Ali Sahmeddini (Turkish Archives of Otorhinolaryngology)
Objective: A pre-anesthetic medication that is ideal for pediatric patients undergoing tonsillectomy should alleviate pediatric anxiety, facilitate the smooth induction of anesthesia, and have an analgesic effect for postoperative care. This study compared the effectiveness of an oral combination of midazolam and ketamine (MK) with an oral combination of chloral hydrate and meperidine (CM) as premedication in pediatric patients undergoing tonsillectomy. Methods: This double-blind clinical trial study was conducted with 68 pediatric patients scheduled to undergo tonsillectomy. The participants were randomly allocated into two groups: the CM group, which received oral premedication of 50 mg/kg chloral hydrate and 1.5 mg/kg meperidine, and the MK mixture group, which received oral premedication of 0.5 mg/kg midazolam and 5 mg/kg ketamine. Various parameters such as separation anxiety, agitation during emergence from anesthesia, postoperative pain, postoperative nausea, and vomiting, as well as respiratory depression within a 6-hour period following anesthesia, were carefully recorded and observed. Results: There were no differences between the two groups in terms of separation anxiety (p>0.05) and post-surgery pain scores (p=0.12). Regarding postoperative agitation, there were significantly more patients in an awake but calm state in the CM group than in the MK (44% vs. 17.64%, p=0.01). The incidence of nausea and vomiting was lower in the CM than in the MK group (47% vs. 76.5%, p=0.02). Conclusion: This study shows that an oral mixture of CM is more suitable as pre-anesthetic medication in pediatric patients undergoing tonsillectomy than a MK.